The microbiological quality of harvested rainwater system in a rural area in Malaysia - Qasim, Ban; Abdul Syukor, Abd Razak; Siddique, Md. Nurul Islam; Suryati, Sulaiman (2017)
Malaysia as a developing nation has experiencing a rapid urbanization. In rural and remote areas where access to safe drinking water is limited so that rainwater harvesting is the most common practice to be used as a supplementary resource.